Electrical Stimulation of Abdominal Muscles to Produce Cough in Spinal Cord Injury: Effect of Stimulus Intensity. (May 2015) - McBain, Rachel A.; Boswell-Ruys, Claire L.; Lee, Bonsan B.; Gandevia, Simon C.; Butler, Jane E.
Background. Surface electrical stimulation of the abdominal muscles, with electrodes placed in the posterolateral position, combined with a voluntary cough can assist clearance of airway secretions in individuals with high-level spinal cord injury (SCI). Objective. To determine whether an increase in stimulus intensity of the trains of electrical stimuli delivered to the expiratory muscles has an increasing effect on a stimulated voluntary cough and to determine at which stimulus intensity a plateau of cough peak expiratory flow occurs. Methods. In 7 healthy individuals with a SCI at and above C7, gastric pressure ( P ga ), esophageal pressure ( P es ), peak expiratory cough flow (PEFcough ), and expiratory volume were measured as participants coughed voluntarily with simultaneous trains of electrical stimuli delivered over the abdominal muscles (50 Hz, 1-s duration). The intensity of the stimulation was increased incrementally. Results : A plateau in PEFcough occurred in all 7 individuals at a mean of 211 ± 29 mA (range 120-360 mA). Peak values reached for P ga, P es, and PEFcough were 83.0 ± 8.0 cm H2 O, 66.1 ± 5.6 cm H2 O, and 4.0 ± 0.4 l/s respectively. Conclusions. The plateau in expiratory cough flow that was associated with increasing expiratory pressures is indicative of dynamic airway compression. This suggests that the evoked cough will be effective in creating more turbulent airflow to further assist in dislodging mucus and secretions.